SPORT FOR ALL AND RECREATION IN THE SOCIETY TRANSITION AND MARKET ECONOMY CIRCUMSTANCES - Budimir Bijelić (Sport Mont, 2007)
Society transition from one organizational system to another always results in great changes within almost all segments of functioning of a preceding ensemble. Organizational changes represent a mode of how any single organization can overcome imbalance and crisis emerged. Organizational changes are commonly caused by imbalance or more precisely disturbance of balance occurred between organizations and surroundings and even within the organization itself. Causes, substance and process of organizational changes represent the three major components to the model of organizational changes. For every single organization (incl. SPORT FOR ALL) it is essential to identify its future position and specify a mode of implementing necessary changes and improvements SPORT FOR ALL organizations and recreation have to conceive and outline these changes which will, as the basis for animation and reception of the participants, have open market opportunities and cooperation in wider regional terms.